Identifying basketball talent in 11–15 year olds using sport search - Afif Rizaldi; Prasetyo, Heru; Caecilia Alma Putri; Abimanyu Wicaksono; Liontin Evangelina Setiawan; Shallma Lushiana; Stevanus Handy Anggoro; Reza Ananda Kenny Firmansyah; Tri Utaminingsih; Anisa Syifane Damayanti; Rafli Feby Putra Tri Prasetyo (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2022)
This study aims to identify the talents and potential of basketball athletes aged 11–15 years who are members of the Tanaka Basketball Club in North Lombok Regency, West Nusa Tenggara Province. The study used a descriptive method with a quantitative approach. The research subjects consisted of 35 athletes, comprising 20 male athletes and 15 female athletes. The instrument used was the Sport Search talent identification test, which included measurements of biomotor abilities such as coordination, strength, explosive power, agility, speed, and endurance. Data analysis was performed using percentage techniques to group the athletes' talent levels. The results showed that of the 35 athletes, 3% were in the highly potential category, 28% in the potential category, 32% in the moderately potential category, 34% in the less potential category, and 3% in the not potential category. These findings indicate that most athletes fall into the moderately potential and less potential categories, thus requiring further targeted training according to the athletes' talent profiles. The Sport Search method has been proven to be a useful initial tool in guiding early-age basketball talent.